Extractive Spectrophotometric Determination of Venlafaxine - Appalaraju, S.; S. Sarasambi, Prakash; B. Karadi, Arvind (Asian Journal of Chemistry, 2010)
Three simple and sensitive extractive spectrophotometric methods (Method A, Method B and Method C) have been developed for the determination of venlafaxine in bulk drug and pharmaceutical formulations. The developed methods involve formation of coloured chloroform extractable complexes of drug with orange-II, bromocresol green and bromophenol blue in acidic medium. Extractable complexes showed absorption maximum at 490 nm, 430 om and 420 nm. Beer's law is obeyed in the concentration ranges of 5–40 μg/mL, 2.5–25 μg/mL and 5–40 μg/Ll respectively. The results of analysis for all three methods have been validated statistically and by recovery studies.